In situ observation and investigation on the formation mechanism of nanocavities in TiO2 nanofibers. Issue 40 (21st September 2016) - Lei, Yimin; Li, Jian; Chen, Fuyi; Wang, Zhan; Liu, Hongwei; Ma, Xiaohua; Liu, Zongwen
Abstract : In this work, the ex situ and in situ TEM investigations on the nanocavities generated at the surface of TiO2 nanofibers reveal that the calcinating atmosphere and crystal structures simultaneously affect the morphology of the nanocavities externally and internally. Abstract : In this work, the formation and evolution mechanism of nanocavities generated on the surface of TiO2 nanofibers during the phase transformation were investigated through ex situ and in situ transmission electron microscopy and X-ray diffraction. The results indicate that the calcination atmosphere plays an important role in the morphology of the nanocavities. For the TiO2 nanofibers calcined in air, the nanocavities show a hexagonal prism morphology, which is related to the phase transformation from TiO2 (B) to anatase. Meanwhile, under vacuum conditions, the nanocavities exhibit an irregular shape due to the occurrence of phase transition from TiO2 (B) to Ti3 O5 . The difference in the morphologies of these nanocavities leads to the different surface areas of the nanofibers and further affects the photocatalytic activity. This work also illustrates that the phase transformation from anatase to rutile is not only related to the activation temperature, but also to the calcination atmosphere. Ultra-high vacuum may retard the transformation.